Patient Involvement During a Pathway of Home-Based Reablement for Older Persons: A Longitudinal Single-Case Study - Ingstad, Kari (J Multidiscip Healthc, 2021)
BACKGROUND: In recent years, home-based reablement has become an increasingly popular way to provide rehabilitation services. This health care service aims to enable older persons to live longer at home while reducing the need for institutionalization. To ensure the provision of high-quality services, there is a continual need for research on issues of user involvement and co-creation during the pathway of the reablement process. PURPOSE: This study focused on user involvement and participation with health care professionals during the reablement process. METHODS: This was a longitudinal, instrumental single-case study, in which one 85-year-old female patient was followed over the pathway of a six-week reablement process. Data were collected at three stages, including the goal-mapping phase, evaluation phase, and three weeks after completing reablement. RESULTS: Our analyses revealed two themes for the goal-mapping phase (dialogue led by the care provider and main goal), three themes for the implementation phase (the home as the preferred setting, little influence on organizational factors, and participation, influence, and motivation), and three themes for the evaluation phase (patient understanding as a precondition, motivated by weak paternalism, and self-determination requires clear communication). CONCLUSION: The patient becomes involved through a partly co-creation process. During this time, they are involved, motivated, and influenced over the pathway of reablement. Health care providers must avoid implementing too much control during the pathway of home-based reablement, as patients have contextual knowledge that care providers do not possess.